Performance evaluation of tubular ceramic membrane for palm oil mill effluent treatment - Wei, Lun Ang; Thivyah Balakrishnan; Thivagaran Veeraiya; Mohammad Haiqal Mohammad Elham; Muhammad Sharafii Faidzal Adlee; Fujioka, Takahiro (Penerbit Universiti Kebangsaan Malaysia, 2020)
Palm oil industry is one of the most important agriculture sectors in Malaysia. However, this industry produces a huge amount of palm oil mill effluent (POME) which contains impurities that will pollute the environment. Hence, POME has to be treated before it can be safely discharged to the environment. This study aims to evaluate the effectiveness of tubular ceramic membranes with different pore sizes (0.2 µm, 450 Da, and 200 Da) for the removal of turbidity and chemical oxygen demand (COD) in POME. It was found that all of the ceramic membranes were capable to achieve more than 99% of turbidity removal through size exclusion mechanism since the particles were larger in size as compared to membrane pores. On the other hand, the reduction of COD was ineffective since the dissolved organic substances in POME could penetrate the membrane and thus resulted in low removal efficiency. Flux decline was recognisable only when treated with the 0.2 µm membrane. It was attributed to its higher initial flux (16 Lm-2h -1) that imposed larger permeation drag and brought more impurities to quickly cover the membrane surface and clog the membrane pores during the initial filtration process. Chemical cleaning was able to recover 77-83% of the flux and this shows that some of the impurities were still persisting in the membrane. The tested membranes were capable to fully remove the suspended solids and could serve as a good pre-treatment process for subsequent COD reduction treatment process.